A hidden technological assumption in patent law: The case of gene patents and the disclosure requirement. (17th August 2019) - Cohen‐Sasson, Or
Abstract: The disclosure requirement in patent law is designed to reveal knowledge regarding a patented invention to allow proper understanding and utilization of that invention. The contention offered here is the presence of an inherent incompatibility between the disclosure requirement and genetic inventions. Genetic inventions are highly contingent on big genetic statistical data (GSD), which is gathered during the commercial phase of a genetic invention. GSD are essential for various purposes, which at least some should be satisfied by the disclosure. However, since GSD can be gathered only at the postapplication period, GSD are not disclosed through the disclosure requirement. Therefore, there is a disclosure‐genetics incompatibility. This incompatibility prevents patent law from fully accomplishing its intended purpose. The origins of this incompatibility can be traced to the structure of the disclosure requirement, a consequence of a hidden technological assumption in patent law regarding the very perception of what is an invention. Patent law perceives all inventions as fully revealed objects and not as semirevealed objects. That creates a difficulty that may be more pervasive than for genetics alone. Thus, acknowledging this technological assumption facilitates the introduction of an insight regarding the fully revealed/semirevealed spectrum regarding inventions in other, nongenetic technological fields.